Concurrent operation of ⟨c + a⟩ slip and twinning under cyclic loading of Ti-6Al-4V. (December 2018) - Lavogiez, C.; Hémery, S.; Villechaise, P.
Abstract: Deformation processes operating in hard/soft grain pairs were characterized in Ti-6Al-4V specimens with a bimodal microstructure submitted to fatigue and dwell fatigue loadings. Concurrent operation of 1st order ⟨c + a⟩ pyramidal slip and slip-stimulated 10 1 ¯ 2 10 1 ¯ 1 deformation twinning was observed in hard grains, resulting from multi-scale strain incompatibilities. The former constitutes a direct experimental evidence of stress redistribution under cyclic loadings while the latter, which is triggered by local stress concentrations due to dislocations pile ups, is detected for the first time. Insights into the crack initiation processes are then discussed. Graphical abstract: Unlabelled Image